Intriguing detection of 12CO molecular emission in a classical Be star - Cochetti, Yanina Roxana (2021)
Context. In the group of B stars with spectroscopic peculiarities, we can find the Be and the B[e] stars. The Be stars are early-type rapid rotators that present, as their principal characteristic, emission lines of hydrogen and singly ionized metals due to the presence of a gaseous envelope. The B[e] stars present in their spectra heterogeneous features that reveal the presence of regions with very different properties in a gaseous and dusty envelope. Aims. Our goal is to study the evolution of the disks around peculiar B stars through the variability of their physical properties and dynamical structure, as well as to set constraints on different models and disk forming mechanisms. Methods. Throughout the last decade, we have carried out temporal monitoring of a sample of objects in the near infrared using spectroscopic facilities at the Gemini and Las Campanas Observatories. In the present work, we focus on the classical Be star 12 Vul, for which also optical spectra have been collected quasi-simultaneously. Results. We observed variability in the hydrogen line profiles of 12 Vul, attributed to dissipating and building-up processes of the circumstellar envelope. Also, we found that this Be star presented the 12CO band heads in emission in one observation. The emission of this molecule has not been previously reported in a Be star, while it is a common feature among B[e] stars. We obtained parameters to describe the 12CO emitting region and propose different scenarios to explain this intriguing emission.